2013
DOI: 10.1001/jamaoto.2013.3559
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and Specificity of Eustachian Tube Function Tests in Adults

Abstract: Objective Determine if Eustachian Tube (ET) function (ETF) tests can identify ears with physician-diagnosed ET dysfunction (ETD) in a mixed population at high sensitivity and specificity and define the inter-relatedness of ETF test parameters. Methods ETF was evaluated using the Forced-Response, Inflation-Deflation, Valsalva and Sniffing tests in 15 control ears of adult subjects after unilateral myringotomy (Group I) and in 23 ears of 19 adult subjects with ventilation tubes inserted for ETD (Group II). Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
91
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(91 citation statements)
references
References 26 publications
0
91
0
Order By: Relevance
“…The best estimates of the sensitivity and the specificity of Valsalva's test (55%/85%) and the Swallowing tests (52%/ 51%) for ETD are reported by Doyle et al 33 The results Pre-BET swallowing test = 12 never, 1 infrequent; week 8 = 1 never, 6 infrequent, 5 always Pre-BET Valsalva = 9 never, 2 infrequent, 1 always; week 8 = 1 never, 6 infrequent, 5 always Poe (2011) TM status recovered to normal in 2/4 with preoperative intact TM, the 2 remaining had grommets inserted when seen at follow-up.…”
Section: Discussionmentioning
confidence: 94%
“…The best estimates of the sensitivity and the specificity of Valsalva's test (55%/85%) and the Swallowing tests (52%/ 51%) for ETD are reported by Doyle et al 33 The results Pre-BET swallowing test = 12 never, 1 infrequent; week 8 = 1 never, 6 infrequent, 5 always Pre-BET Valsalva = 9 never, 2 infrequent, 1 always; week 8 = 1 never, 6 infrequent, 5 always Poe (2011) TM status recovered to normal in 2/4 with preoperative intact TM, the 2 remaining had grommets inserted when seen at follow-up.…”
Section: Discussionmentioning
confidence: 94%
“…Although the importance of the intact ET for the ventilation and health of the middle ear mucosa has been known for many centuries, no diagnostic gold standard tool for ET diseases is currently available. [2] Identification of ETD is difficult, and a recent systematic review identified wide variations in the diagnostic criteria employed. [16] In recent years, new therapeutic approaches for chronic obstructive ETD have been developed in several countries.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms are often exacerbated with atmospheric pressure changes. [1,2] Patients may also experience pressure, clogged or underwater sensation, popping, ringing and crackling. Chronic ETD may result in variable middle ear pathologies, such as serous otitis media, chronic otitis media, tympanic membrane retractions, and cholesteatoma.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…paratubal muscle-ET vector relationships) of the ET system 6 . Using a variety of different ETF test protocols, past research reported that constitutive ETF is: poorer in patients with OME and other ME diseases when compared to age-matched subjects without disease (by manometric testing) 7-11 ; poorer in young children when compared to adults (by pressure chamber testing) 12 ; and, at all ages, downgraded during periods with extant co-morbid disease conditions that provoke inflammation in or around the ET (by 9 Step testing) 13,14 .…”
Section: Introductionmentioning
confidence: 99%